Hubungan Efikasi Diri Dan Dukungan Sosial Dengan Burnout Pada Perawat - Harnida, Hanna (Persona:Jurnal Psikologi Indonesia, 2015)
The purpose of thid study is to test the relationship between self efficacy and social support by burnout to nurses. The variables of the the study are measured by using self efficacy scale , social support scale and burnout scale. The subjects of the study are 60 employed nurses, aged between 20 – 40. The input data is analyzed by using Spearmann Rho. The result show that shows that self efficacy doesn’t have relation with burnout , showing Rhoo = 0,002 and p = 0,986. Social support doesn’t have relationship doesn’t have relationship with burnout , where are Rhoo = 0,089 to p = 0.498. On different study by mannwhitney = 444,500 and p = 0,946 show that self efficacy difference between senior and medior. Social support of Mann Whitney U test = 211,500 and p = 0,000 show that there is significant different between senior and medior. Burnout with mann whitney =449,500 and p =0,994 (p>0,055)showsno relation between senior and medior.